CLOUD COMPUTING: A COMPREHENSIVE GUIDE TO MODERN INFRASTRUCTURE - Narasimha Rao Oruganti, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This comprehensive article explores the evolving landscape of cloud computing, examining its fundamental characteristics, service models, deployment strategies, and future trends. The article investigates how cloud computing has transformed organizational IT infrastructure, enabling unprecedented scalability, cost efficiency, and operational agility. Through a detailed examination of various implementation models, including Infrastructure as a Service, Platform as a Service, and Software as a Service, the analysis reveals the significant impact across industries, from financial services to healthcare and manufacturing. The article encompasses emerging trends such as edge computing, artificial intelligence integration, and sustainable practices while addressing critical security, compliance, and integration challenges. Special attention is given to the adoption patterns of different deployment models - public, private, hybrid, and multi-cloud approaches - highlighting their benefits and implementation considerations.